Role of homovanillic acid esters in the regulation of skin inflammatory pathways and their effect on tight junction protein expression - Cervantes Recalde, Maria Fernanda; Bogensperger, Elena Zoe; Hans, Joachim; Stuhlmann, Dominik; Somoza, Veronika; Lieder, Barbara (Frontiers in Pharmacology, 2025)
IntroductionIn the context of epidermal inflammation, the inflammatory response not only involves the release of inflammatory cytokines like interleukin 8 (IL-8), but also modulation of tight junction protein expression levels. Previous studies showed that the tight junction protein claudin 1 (CLDN1) is upregulated during tumor necrosis factor α (TNFα)-induced inflammation by capsaicin in keratinocytes in a transient receptor potential channel vanilloid 1 (TRPV1)-dependent manner. However, the caveat with TRPV1 ligands is the undesired pain response elicited by the activation of neuronal TRPV1 channels. In this study, we hypothesized that also less or non-pungent homovanillic acid esters as structural analogs of capsaicin target CLDN1 upregulation during inflammation.MethodsWe aimed to identify beneficial structural characteristics by selecting homovanillic acid esters with different aliphatic tail structures and screening them for CLDN1 upregulation at early stages of TNFα-induced inflammation in basal keratinocytes.ResultsCLDN1 expression was upregulated independently of TRPV1 by compounds with a tail of 5 or 6 C-atoms, regardless of the presence of ramifications and double bonds with a maximum fold change of 2.05 ± 0.22 against control. The induction of CLDN1 expression was accompanied by increased expression of the differentiation marker involucrin (IVL).DiscussionThe results suggest that the homovanillic ester-induced CLDN1 upregulation is a result of increased differentiation of the basal keratinocytes towards the keratinocyte morphology present in the stratum granulosum (SG), where tight junctions are formed. In conclusion, homovanillic acid esters with a 5 or 6 C-atom long aliphatic chain induced CLDN1 expression, thereby stimulating keratinocyte differentiation, independent from TRPV1 activation.